Bridging Continents: The Expansion and Establishment of the House Bunting (Emberiza sahari) from North Africa to Europe - Antonio-Román Muñoz; Darío Delgado; Pablo Ortega; Julio Ortega; Antonio Sepúlveda; Pedro Barón; Eva Bratek; Javier Elorriaga; Cristina Malia; Ricky Owen; Miguel Puerta; Alejandra Cerezo; et al. (Birds, 2025)
Range expansions driven by global warming are increasingly documented, particularly in birds and insects. The House Bunting, a species native to North Africa, has recently established the first confirmed breeding population in mainland Europe in Algeciras, southern Spain. This study presents the results of the first systematic survey of this population, conducted in December 2024. Using a standardized survey method across a grid of hexagonal sampling units, we recorded a minimum of 18 individuals, including juveniles, indicating both successful reproduction and possible new arrivals. Observations were concentrated in low-rise urban areas, mirroring the species’ preferred habitats in Morocco. The presence of individuals with juvenile plumage in December suggests an extended breeding season, which may facilitate population growth. Given the geographical proximity to North Africa and predicted increases in aridity due to climate change, further expansion into Iberia appears likely. Although no immediate ecological impacts have been detected, the potential for interactions with resident species justifies continued monitoring. This study provides a baseline for assessing the establishment and growth of this population, contributing to a broader understanding of how climate change influences species distributions and the colonization dynamics of expanding bird populations.